SURVEI DAN EDUKASI PENGGUNAAN PESTISIDA DI RUMAH TANGGA DAN DAMPAKNYA TERHADAP KESEHATAN PADA MASYARAKAT DI NAGARI PANASAHAN KOTA PAINAN - Cimi Ilmiawati; Mohamad Reza (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Various pesticides are widely used in households to control animals and pests. Pesticides consist of chemicals known to be harmful to health, so their use must be regulated in a certain way to avoid acute and chronic toxicity to humans. The purpose of this activity is to conduct a survey regarding the knowledge and behavior of a community in Nagari Panasahan, Painan, regarding the use of pesticides and their impact on health and to conduct education on how to properly use pesticides. Assessment of participant knowledge and behavior regarding pesticide use was carried out using a questionnaire with 28 questions. A total of 35 participants took part in the educational program. The questionnaire response analysis showed that most of the participants were housewives, had a primary-secondary education, had limited income, used more than one type of pesticide to control nuisance animals, and had limited knowledge about the chronic toxicity pesticides and about how to protect health. Environmental health experts provide educational materials on pesticides, their effects on health and prevention efforts, followed by interactive discussions. Further evaluation is needed to determine whether the program is successful in modifying pesticide use in this community.